A study on non-compliance in tuberculosis cases towards the directly observed treatment short course under RNTCP in Kanpur Nagar - Srivastava, Kuldeep; Gupta, Abhishek; Saxena, Ruchi; Sharma, R. P.; Midha, Tanu (International Journal Of Community Medicine And Public Health, 2017)
Background: The goal of Revised National Tuberculosis Control Programme (RNTCP) is to achieve cure rate of at least 85% and to detect at least 70% of the new smear positive cases of tuberculosis (TB). A very high rate of compliance to treatment is required to achieve the target and to prevent the drug resistance. The objective of the study was to study the magnitude and reasons of non-compliance in TB patients towards directly observed treatment short course (DOTS) in Kanpur Nagar. Methods: Multistage random sampling technique was used to select the study subjects from the two designated microscopy centres (DMC). Information regarding treatment compliance and patient satisfaction was elicited and recorded in the predesigned and pretested questionnaire, analysis was done using SPSS and percentages was used to draw the results. Results: Out of total 300 study subjects, 41(13.67%) were non-compliant during treatment. Majority of non-compliant study subjects were aged more than 50 years (30.23%), skilled workers (29%), belonged to socioeconomic class III (22.9%), Muslims (19.36%) and educated upto high school (16.33%). The most common cause of non-compliance in the present study was symptomatic relief during treatment (73.20%) followed by intolerance to medications (24.40%). Conclusions: Compliance to the drug regimen under RNTCP plays a vital role in the cure of the TB cases. Non-Compliance rate being high in the present study, health education of the community at large and regular follow up of all defaulters, to find out the reasons for default and measures to reduce them, requires more emphasis to achieve the goal of RNTCP.